Durvalumab and pembrolizumab in advanced biliary tract cancer: a reconstructed patient-level mimic head-to-head comparative analysis - Wang, Bi-Cheng; Kuang, Bo-Hua; Lin, Guo-He; Fu, Chen (Frontiers in Immunology, 2024)
BackgroundThe addition of durvalumab or pembrolizumab to gemcitabine and cisplatin (GP) has been approved to statistically improve survival outcomes in patients with advanced biliary tract cancer. However, since the survival time was only prolonged by about two months, doubts have been raised. In this analysis, we aimed to evaluate the efficacy of combining durvalumab or pembrolizumab with GP chemotherapy.MethodsRecords were identified through a formal search of PubMed and Web of Science. The TOPAZ-1 and KEYNOTE-966 trials were definitively included. Patient-level overall survival (OS) and progression-free survival (PFS) data were reconstructed and analyzed using a one-stage approach.ResultsThe immunotherapy plus GP chemotherapy group showed superiority over the GP chemotherapy group (OS: HR 0.83, p < 0.001; PFS: HR 0.88, p = 0.009). The survival outcomes were similar between the durvalumab and pembrolizumab groups (OS: HR 1.02, p = 0.83; PFS: HR 0.95, p = 0.53). In the subgroup analysis, the gemcitabine-maintenance group significantly prolonged the OS compared to the gemcitabine-limited-to-8-cycles group (OS: HR 0.86, p = 0.007). Neither the durvalumab nor pembrolizumab groups statistically improved the OS compared to the gemcitabine-maintenance group. In contrast, the durvalumab and pembrolizumab groups significantly improved OS compared to the gemcitabine-limited-to-8-cycles group.ConclusionsBased on this mimic head-to-head analysis, we are convinced that durvalumab and pembrolizumab benefit patients with biliary tract cancer. However, despite the statistically significant differences, the moderate progress made in OS and PFS might still be considered inadequate. It is crucial for clinicians to identify the precise subgroup population that could benefit most from immunotherapy and develop more strategies for those who might not respond well to immunotherapy.